2020
DOI: 10.2147/ott.s227826
|View full text |Cite
|
Sign up to set email alerts
|

<p>MiR-195-5p Inhibits Malignant Progression of Cervical Cancer by Targeting YAP1</p>

Abstract: Purpose: Our previous studies have shown that miR-195 is reduced in cervical cancer tissues, and that upregulation of miR-195 suppressed cervical cancer cell growth and induced a cell cycle block. In this study, we aimed to further elucidate the mechanism of action between miR-195-5p and Yes-associated protein 1 (YAP1) in the malignant progression of cervical cancer. Methods: MiR-195-5p and YAP1 were detected using qRT-PCR in cervical cancer cells transfected with miR-195-5p mimics or inhibitor. Cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…MicroRNAs (miRNAs) are implicated in tumorigenesis by binding to the 3' UTR of target mRNA and repressing their translation. Diverse miRNAs can participate in CC development as tumor-suppressive miRNAs or oncomiRs [6][7][8][9]. For instance, miR-145-5p targets fascin to impede cancer cell migration and invasion in CC [6].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are implicated in tumorigenesis by binding to the 3' UTR of target mRNA and repressing their translation. Diverse miRNAs can participate in CC development as tumor-suppressive miRNAs or oncomiRs [6][7][8][9]. For instance, miR-145-5p targets fascin to impede cancer cell migration and invasion in CC [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, including own research, have confirmed that dysregulation of YAP1 results in tumorigenesis, including in TNBC ( 18 – 21 ). Several miRNA molecules, such as miR-195-5p ( 22 ), miR-630 ( 23 ) and miR-1285-3p ( 24 ) were identified as YAP1 regulators. Nevertheless, further understanding of the post-transcriptional control of YAP1 in TNBC is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…indicating that miR-1258 can be used as a therapeutic target for human CRC (17). Another study showed that miR-195-5p can downregulate the expression of YAP1 and miR-195-5p-mediated downregulation of YAP1, which impedes genesis and development of tumors in CRC (18). For miR-672-3p, it has been noted that miR-672-3p can serve a role of tumor suppressor in a number of types of cancer (19).…”
Section: Discussionmentioning
confidence: 99%